Reprogramming of bone marrow-derived mesenchymal stem cells into functional insulin-producing cells by chemical regimen - Wang, Qiwei (e-Century Publishing Corporation, 2012)
Beta-cell transplantation is considered to be the most effective approach to cure type 1 diabetes (T1D). Unfortunately, the scarce availability of donor tissue limits the applicability of this therapy. Recent stem cell research progress shows stem cell therapy may be a potential means to solve this problem. Bone marrow-derived mesenchymal stem cells (MSCs) are self-renewable and multipotent adult stem cells which can differentiate into the three germ layers. Here we aimed to investigate whether MSCs could be reprogrammed into insulin-producing cells (IPCs). We isolated and characterized MSCs obtained from rat bone marrow. Then MSCs were induced to transdifferentiate into IPCs under specific conditions containing high concentrations of glucose, activin A, all-trans retinoic acid, and other maturation factors. The induced cells expressed multiple genes related to pancreatic beta-cell development and function, such as insulin1, glucagon, Pdx1, Pax6, and Glut-2. Insulin1 and C-peptide production were identified by immunocytochemistry. In vitro glucose challenge studies showed the induced cells secreted insulin in a glucose-dependent manner, as do normal pancreatic beta-cells. Transplantation of these MSC-derived insulin-positive cells could reverse the hyperglycemia of streptozotcin (STZ)-induced diabetic rats. These results demonstrated that MSCs could be reprogrammed into IPCs and might be a potential autologous cell source for transplantation therapy of T1D.